A Preliminary Study to Understand the SMEs’ Readiness on IoT in Malaysia - Mohamad Faizal Ahmad Zaidi; H.M. Belal (International Journal of Accounting, Finance and Business, 2019)
IR4.0 is the fourth industrial revolution that has started to take effects on the current domain of production systems. It was caused by the advancement of digitalization systems and integration with IoT, and smart objects. Due to changing nature of technology, the new source of capabilities will emerge, while the existing one will become irrelevant for sustaining competitive advantage. As a result, firms worldwide including SMEs have left without many options, but to prepare and get ready with the change. As a part of major pillars of technological advancement that make happens the IR4.0, this study is focusing on the issues on IoT readiness among SMEs in Malaysia. The data was collected from the SMEs and descriptively analyzed with the SPSS v.20 statistical package. The findings have suggested the respondents are quite optimism with the benefits of IoT, but lacking of innovativeness to pioneer the introduction. In addition, although the respondents do not feel discomfort with IoT, they do seem undecided either to trust it or not. It was also found that top managements feel more optimism with IoT, but at the same time also feel more insecure with it. With these findings, it was suggested that the SMEs need more information and training to increase their knowledge for successful adoption of IoT in Malaysia. A few suggestions to improve the respondents’ awareness on IoT and the readiness level are also highlighted.